STUDI KASUS MATERI PERTUMBUHAN DAN PERKEMBANGAN TUMBUHAN DI SMA 12 BANDA ACEH (Lantanida Journal, 2017)
Learning activities are planned educational activities to gain knowledge and insight, and it can change a person's behavior toward maturity. Learning also processes that affect the understanding of the value that predispose a person to think, act and behave. Biology lesson that SMA 12 Banda Aceh is not maximized penerapaan pedagogical competence and professional competence in accordance learning Permendiknas No. 16 of 2007 on Academic Qualification Standards and Teacher Competence part B is to develop teaching materials. Then the teaching materials are not in accordance with the level of experience and ability of the students' characteristics has reduced student motivation. One way to improve students 'motivation to increase interest in learning, can be done by providing teaching materials in accordance with the level of experience and ability of the students' characteristics.
Keywords: Learning Activities; Students Motivation; Teaching Materials.